Formal Mental Models of Junior High School Students in Understanding the Concept of Integers - Kusumasari, Vita; Mutina, Mutina; Sudirman, Sudirman (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
Mental models are internal representations students form about a concept, which can be inferred through their external representations. This study aims to describe the characteristics of junior high school students' formal mental models in understanding the concept of integers. Conducted in a class of 44 seventh-grade students, this qualitative study employed a case study methodology. Subjects were selected using a purposive sampling, with two subjects chosen for in depth exploration and interviews. Data were analyzed using the Miles and Huberman model, encompassing data condensation, data presentation, and conclusion drawing. The results revealed that the students at the formal mental model level demonstrated the characteristics of being able to place positive integers, zero, and negative integers on a number line, compare positive and negative integers, compare two negative integers, sort integers, add and subtract integers, and sort them accordingly. By refining the characteristics of mental models of value and order of integers, and integrating Bofferding's ideas on the mental model of value and order of integers and mental model of directed magnitude, this study successfully expands the theoretical framework of students' mental models in understanding the concept of integers, extending it to include addition and subtraction operations. Practically, it provides educators with insights into the characteristics of formal mental models that seventh-grade students need to master, supporting the development of meaningful instructional strategies to strengthen students’ conceptual understanding and promote the advancement of mental models to the formal level. In addition, these findings serve as a reference for future research on students' mental models in understanding integers and performing integer operations. Abstrak Model mental diartikan sebagai representasi internal yang dimiliki siswa mengenai suatu konsep yang kemudian dapat diketahui melalui representasi eksternal. Penelitian ini bertujuan untuk mendeskripsikan karakteristik model mental formal siswa SMP dalam memahami konsep bilangan bulat. Penelitian ini dilakukan di kelas VII SMP yang terdiri dari 44 siswa. Metode penelitian yang digunakan adalah kualitatif dengan jenis penelitian studi kasus. Pemilihan subjek menggunakan teknik purposive sampling, yakni terdapat 2 subjek untuk dieksplorasi dan diwawancarai. Teknik analisis data menggunakan model Miles dan Huberman meliputi kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa karakteristik siswa pada level model mental formal adalah dapat menempatkan bilangan bulat positif, nol, dan bilangan bulat negatif pada garis bilangan, dapat membandingkan bilangan bulat positif dan bilangan bulat negatif, dapat membandingkan dua bilangan bulat negatif, dapat mengurutkan bilangan bulat, dapat menjumlahkan dan mengurangkan bilangan bulat sekaligus mengurutkannya. Dengan mempertajam karakteristik model mental nilai dan urutan bilangan bulat, serta mengintegrasikan gagasan Bofferding tentang model mental nilai dan urutan bilangan bulat dan model mental besaran terarah, penelitian ini berhasil memperluas kerangka teori tentang model mental siswa dalam memahami konsep bilangan bulat, sehingga mencakup pula operasi penjumlahan dan pengurangan. Secara praktis, studi ini memberikan wawasan kepada pendidik mengenai karakteristik model mental formal yang perlu dikuasai oleh siswa kelas tujuh, mendukung pengembangan strategi pengajaran yang bermakna untuk memperkuat pemahaman konseptual siswa dan mendorong perkembangan model mental mereka ke tingkat formal. Selain itu, temuan ini dapat dijadikan acuan untuk penelitian lebih lanjut mengenai model mental siswa dalam memahami bilangan bulat dan melakukan operasi bilangan bulat.